Pengaruh Stres melalui Sing-A-Song Stress Test terhadap Selective Attention pada Dewasa Awal - Trisna Setiatama; Sri Kusrohmaniah (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2017)
Selective attention is part of the executive function and controlled by the frontal lobe. Previous research suggests that selective attention can be affected by stress. Stress can interrupt frontal lobe performance. Nevertheless, no research in Indonesia has tested about this matter. This study aimed to determine the effect of stress through Sing-a-Song Stress Test on selective attention in early adulthood. The hypothesis of this study is that stress can decrease selective attention. A between-subjects design was applied in this study. A number of 35 participants with an age range from 17 to 21 years old were randomly assigned into an experimental group (n = 17) and control group (n = 18). Selective attention score was measured using Computerized Stroop Color-Word Test. Positive Affect and Negative Affect Schedule were used to conduct a manipulation check. Independent-Samples T Test explained no significant effect of stress on selective attention (t = .158; p > .05).